VARIABILITY, HERITABILITY, AND CORRELATIONS AMONG GRAIN YIELD AND RELATED TRAITS IN HULLESS BARLEY ACCESSIONS - N. Dyulgerov; B. Dyulgerova (Trakia Journal of Sciences)
The aim of the present study was to investigate the variability, heritability and correlation between grain yield and yield-related traits of hulless accessions of spring barley under Southeast Bulgarian conditions. The research work was conducted in the experimental field of the Institute of Agriculture - Karnobat, South-eastern Bulgaria during the 2016 and 2017 growing seasons. The trail consisted of 20 six-rowed hulless barley accessions from ICARDA. A significant variation of grain yield and yieldrelated traits among the studied hulless barley accessions was found. The values of broad-sense heritability were from 1.81% for grain yield to 81.84% for the number of spikelets per spike. The number of spikes per plant had a direct positive effect on grain yield of hulless spring barley in both growing seasons. In a condition of water stress (the second year of study), the weight of grains per spike shows the highest direct effect on grain yield. Since the number of spikes per plant and weight of grains per spike had low heritability, these traits can be used as additional traits for selection for improving grain yield in the hulless barley breeding program of hulless barley only if the selection be practiced in later generations in replicated trials.